2019
DOI: 10.1038/s41598-019-52371-7
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based monitoring of groundwater depletion in California’s Central Valley

Abstract: Range change data, obtained from Synthetic Aperture Radar satellites, form the basis for estimates of aquifer volume change in California’s Central Valley. The estimation algorithm incorporates a function penalizing changes far from known well locations, linking the aquifer volume changes to agricultural, industrial, and municipal pumping within the Tulare basin. We show that the range changes are compatible with the hypothesis that the source of aquifer volume changes are variations in effective pressure arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…Due to the difficulty of the inverse problem it is important to devise appropriate regularization schemes to stabilize the process of estimating a solution. One particularly useful approach for volume changes that are induced by fluid extraction and injection into a reservoir, is a regularization or penalty term that favors volume changes near known well locations (Vasco et al 2010, Rucci et al 2013, Vasco et al 2019. Such a penalty term utilizes the fact that the effective pressure changes surrounding the well are driving the volume changes within the reservoir.…”
Section: Data Interpretation and Inversion Methodsmentioning
confidence: 99%
“…Due to the difficulty of the inverse problem it is important to devise appropriate regularization schemes to stabilize the process of estimating a solution. One particularly useful approach for volume changes that are induced by fluid extraction and injection into a reservoir, is a regularization or penalty term that favors volume changes near known well locations (Vasco et al 2010, Rucci et al 2013, Vasco et al 2019. Such a penalty term utilizes the fact that the effective pressure changes surrounding the well are driving the volume changes within the reservoir.…”
Section: Data Interpretation and Inversion Methodsmentioning
confidence: 99%
“…The early development of many geodetic techniques in the Earth sciences was for the study of natural hazards such as volcanoes (Dzurisin 2007) and earthquakes with their correspondingly larger ground deformation than that due to geothermal activity. However, several techniques have been adopted to study such processes as subsidence due to groundwater withdrawal (Vasco et al 2019), ground movement induced by the sequestration of carbon dioxide (Vasco et al 2020), deformation due to oil and gas development (Fielding et al 1998), as well as to study surface displacements associated with geothermal production. LiDAR (Eitel et al 2016), is one emerging technology that we shall not discuss.…”
Section: Commonly Available Geodetic Methodsmentioning
confidence: 99%
“…Remote sensing data have also been used in monitoring other variables in land and resource use systems, to assess soil salinity (Ivushkin et al 2018), aquifer volume and groundwater drought (Thomas et al 2017;Vasco et al 2019), and temperature warming over landscapes and oceans (FEWS NET 2018a, b). It has been used to identify hotspot areas of high N inputs and to model biogeochemical processes of N flows in agricultural systems (Liu et al 2020).…”
Section: Monitoring Non-vegetation Variables In Agriculturementioning
confidence: 99%
“…Thomas et al (2017) used NASA's GRACE satellite mission data to quantify groundwater storage deficits in California's central Valley, enabling them to capture groundwater drought. Using InSAR, Vasco et al (2019) could better match the identified change in aquifer volume in the valley with point observations, an improvement compared to using only the GRACE data.…”
Section: Monitoring Non-vegetation Variables In Agriculturementioning
confidence: 99%